Pengaruh Komunikasi, Budaya Organisasi Dan Kemampuan Sumber Daya Manusia Terhadap Efektivitas Kerja Pegawai Kantor Kecamatan Kalumpang Kabupaten Mamuju - Widya Aulia; Agus Halim (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Employee performance plays an important role in determining the quality of public services and governance processes, especially at the sub-district level, which acts as the final part of the state administration system. At the Kalumpang Sub-district Office, Mamuju Regency, several challenges such as difficult geographical conditions, limited facilities, and differences in employee backgrounds can affect overall performance. Issues related to employee performance are not only related to the achievement of work targets, but also reflect the organization's ability to communicate internally, build a good working atmosphere, and maximize the potential of its employees. Therefore, this research is important to understand in depth the internal factors of the organization that affect employee performance.This study aims to analyze the influence of communication, organizational culture, and human resource capabilities on employee performance at the Kalumpang Subdistrict Office, both individually and collectively.The approach used is quantitative with a survey method, in which all employees are research respondents. Data is collected through questionnaires based on relevant theoretical indicators, which have been tested for validity and reliability. The analysis is carried out using multiple linear regression to identify the level of relationship and the magnitude of the influence of each independent variable on the dependent variable, thereby producing an overview. This study shows that communication has a positive and significant impact on employee work effectiveness. This indicates that clear instructions, accurate information delivery, and the intensity of communication between superiors and employees are still the main factors in determining success in carrying out tasks. In addition, organizational culture also has a major influence on work effectiveness, especially in terms of discipline, commitment to work, and teamwork, which have not been fully internalized evenly in the Kalumpang Subdistrict Office environment. Human resource capabilities have been proven to have the greatest influence on employee work effectiveness.